Advertisements as reflections of ideals:Shari’ah-compliant advertisements for the Muslim target audience - Mokhtar, Aida; Samsudin, Sofiah; Sawari, Fuad (2016)
Shariah principles should be used as guidance for Islamic advertising to the Muslim market. The Muslim market ought to be conveyed in an Islamic manner as advertising should be perceived as a form of education other than having the commercial objectives.